Democracy, economic growth, and income inequality: Evidence from province level data - Irwan Trinugroho; Aldy Fariz Achsanta; Putra Pamungkas; Nugroho Saputro; Sari Yuniarti (Cogent Economics & Finance, 2023)
Democracy is an essential aspect in national-level governance to safeguard human rights and provide equal distribution of wealth among citizens that are also expected to bolster more rapid economic growth. However, the extant literatures show mixed result in providing evidence of how democracy will impact economic growth. In this paper, we, therefore, empirically examine the impact of democracy on economic growth and income inequality at the regional level by studying provinces in Indonesia. A panel data estimation is employed with 335 province-year observations to test our empirical model covering 34 provinces. We find that overall democracy is a detrimental factor to regional economic growth as higher level of democracy needs substantial cost to finance. However, our study reveals that democracy help reduce inequality across provinces as it may open up the possibilities to get more education for marginalized people which then implies for higher income for those people. Several policy implications are discussed.
Keywords: 330; democracy; economic growth; income inequality; indonesia; province